Aids in the Black Community: Public Health Implications - Joseph, Stephen C. (1988)
As of the end of September 1988, 16,600 cases of acquired immunodeficiency syndrome (AIDS) have been reported in New York City, including 5,248 cases among blacks, 32 percent of the total. Of these, 4,220 (80 percent of adults) are men, 1,028 (19 percent of adults) are women, and 195 are children. The major source of the spread of human immunodeficiency virus (HIV) infection within the black community is the intravenous (IV) drug user. Half of New York City's 200,000 IV drug users are estimated to be black; almost half of the women infected with AIDS through sexual contact with IV drug users are black. Every option for breaking the AIDS-IV drug abuser connection must be explored. AIDS among blacks is especially charged with the potential for discrimination or widespread backlash. AIDS education efforts must be increased, and legislation to protect against unauthorized disclosures of confidential health records must be supported. Comprehensive education programs must destigmatize AIDS among health care workers. To keep up with the epidemic, a national prevention strategy must consist of a massive national public health education program; voluntary, confidential counseling and HIV antibody testing expanded into every public and private clinical facility; and major efforts to curtail AIDS transmission by the IV drug user.